Applications of Ruthenium Complex in Tumor Diagnosis and Therapy - Lin, Ke; Zhao, Zi-Zhuo; Bo, Hua-Ben; Hao, Xiao-Juan; Wang, Jin-Quan (Frontiers in Pharmacology, 2018)
Ruthenium complexes are a new generation of metal antitumor drugs that are currently of great interest in multidisciplinary research. In this review article, we introduce the applications of ruthenium complexes in the diagnosis and therapy of tumors. We focus on the actions of ruthenium complexes on DNA, mitochondria, and endoplasmic reticulum of cells, as well as signaling pathways that induce tumor cell apoptosis, autophagy, and inhibition of angiogenesis. Furthermore, we highlight the use of ruthenium complexes as specific tumor cell probes to dynamically monitor the active biological component of the microenvironment and as excellent photosensitizer, catalyst, and bioimaging agents for phototherapies that significantly enhance the diagnosis and therapeutic effect on tumors. Finally, the combinational use of ruthenium complexes with existing clinical antitumor drugs to synergistically treat tumors is discussed.